PENGARUH LUAS TANAM DAN PENERAPATAN TEKONOLOGI BUDIADAYA KEDELAI TERHADAP PRODUKTIVITAS LAHAN DI KABUPATEN LOMBOK BARAT - I DEWA GEDE SUARTHA; MADE SUMA WEDASTRA; I GUSTI AGUNG DIDIT EKA PERMADI (Universitas Mahasaraswati K. Mataram, 2022)
The research entitled the effect of planting area, application of soybean cultivation technology on land productivity in West Lombok Regency focuses on the problem of wanting to know the application of soybean cultivation technology and the effect of planting area and application of three categories of soybean cultivation technology (poor, good, very good) on land productivity. The method of determining respondents was done by purposive random sampling as many as 60 people with multiple linear regression data analysis, one quantitative variable and two dummy variables. The results of data analysis showed that the application of soybean cultivation technology in West Lombok Regency was classified as good with a score of 639 with an average production of 7 quintals per planted area (55 acres) or 12 quintals per hectare. Meanwhile, the planting area and the application of good and very good soybean cultivation technology significantly affect the productivity of the land either simultaneously or partially at the 5% level of significance. Partially, the planting area has a dominant effect on land productivity with a regression coefficient of 0.098. This means that if the planting area changes by 1%, then the productivity of the land will change by 0.098%. Then the application of good and very good soybean cultivation technology also had a significant effect on land productivity at a significant level of 5% with regression coefficients of 2.669 and 3.467, respectively. This means that if the conditions for applying soybean cultivation technology change by 1%, it will cause changes in land productivity of 2.669% for changes in good cultivation technology and 3.467% for changes in very good technology.